Inhibitory effect of (−)-epigallocatechin-3-gallate and bleomycin on human pancreatic cancer MiaPaca-2 cell growth - Bimonte, Sabrina (Infect Agent Cancer, 2015)
BACKGROUND: Human pancreatic cancer is currently one of the deadliest cancers with high mortality rate. It has been previously shown that (−)-epigallocatechin-3-gallate (EGCG), the most abundant catechin found in green tea, has showed suppressive effects on human pancreatic cancer cells. Bleomycin, (BLM), an anti-cancer chemotherapeutic drug that induces DNA damage, has antitumor effects by induction of apoptosis in several cancer cell lines and also in pancreatic cancer cells. The present study investigated for the first time, the inhibitory effect of EGCG and BLM on pancreatic cancer cell growth. METHODS: Using the pancreatic cancer cell lines MIA PaCa-2 cells the efficacy and synergism of EGCG and BLM were evaluated by in vitro tests. Inhibition of cell proliferation was determined by MTT assay. Mitochondrial depolarization was performed with JC-1 probe. Viability and apoptosis were determined by Flow Cytometry with annexin V, propidium iodide staining and DNA fragmentation assay. RESULTS: Cell proliferation assay revealed significant additive inhibitory effects with combination of EGCG and BLM at 72 h in a dose dependent manner. The combination of EGCG and BLM induced cell cycle S-phase arrest and mitochondrial depolarization. Viability, apoptosis and DNA fragmentation assay indicated that the combination of EGCG and bleomycin potentiated apoptosis. CONCLUSIONS: Our results indicate that EGCG and BLM have additive anti-proliferative effects in vitro by induction of apoptosis of MIA PaCa-2 cells. This combination could represent a new strategy with potential advantages for treatment of pancreatic cancer. To date, this is the first report published of the inhibitory effect of EGCG and BLM on human pancreatic cancer MIA Paca-2 cell growth.